Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan dengan Disiplin Kerja sebagai Variabel Intervening pada PDAM Kota Solok - Arrasyd, Jourdi; Wijaya, Ronni Andri (Lembaga Yasin AlSys, 2024)
This research aims to determine and attempt to analyze the influence of compensation and work motivation on employee performance with work discipline as an intervening variable at PDAM Kota Solok. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are Solok City PDAM employees. The research results found that there is a positive and significant influence between compensation and work motivation on work discipline. There is a positive and insignificant influence between Compensation and Work Motivation on Employee Performance. There is a positive and significant influence between Work Discipline on Employee Performance. Work Discipline is able to mediate Compensation on Employee Performance. Work Discipline is able to mediate Work Motivation on Employee Performance.